Determinan Minat Petani Dalam Budidaya Kedelai Sesuai Standard Operating Procedures (SOP): Sebuah Analisis Regresi Linier Berganda - Eka Mustiyanti; Siti Nurlaela; Sujono Sujono (University of Jember, 2022)
This study aims to determine the interest of farmers in growing soybeans according to the Standard Operating Procedure (SOP), as well as the factors that influence it. The study was conducted from January to July 2022 at the Sriharjo Village Farmers Group, Kapanewon Imogiri, Bantul Regency. This study uses quantitative methods. Determination of respondents who became the sample was determined using the proportional random sampling technique of as many as 41 respondents. The data analysis technique used descriptive analysis and multiple linear regression analysis. The results of the study showed that the factors studied, namely age, education, land area, the role of extension workers, and assistance for farming facilities had a simultaneous effect on farmers' interest in soybean cultivation according to the Standard Operating Procedure (SOP) with an F-count of 3.323 (Sig 0.015) and coefficient of determination (R2) 32.2%. The factor that partially has a significant effect on farmers' interest in soybean cultivation according to the Standard Operating Procedure (SOP) is the education factor. The results of the study are used to develop plans for empowerment activities. Empowerment activities have succeeded in increasing the knowledge of farmers by 53.61% and attitudes by 14.45%.